(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Diabetes foot infection due to gangrene is the most common cause of prolonged hospitalization and amputation of theirlimbs. The present study was conducted to assess risk factors in the surgical management of diabetic foot ulcer.Materials & Methods: 88 cases of diabetic foot ulcer of both genders were enrolled. Previous history of diabetes, wound healing,ulcers and boils in other part of the body were recorded. Parameters such as Wagner's classification, type of operations performedwere recorded.Results: Out of 88 patients, males were 48 and females were 40.Wagner classification grade 0 was seen in 5, grade 1 in 5, grade 2 in14, grade 3 in 16, grade 4 in 20 and grade 5 in 28 patients. The difference was significant (P< 0.05). Gangrene was seen in 20,cellulitis in 15 and ulcer in 53 patients. Bacteria isolated were staphylococcus aureus in 64%, Beta haemolytic streptococci in 6%,gram negative organisms in 20% and anaerobic cocci in 10%. The difference was significant (P< 0.05). Management done wasincision and drainage in 3, amputation in 45, debridement in 20, transmetatarsal in 8, below knee amputation in 7 and above kneeamputation in 5 patients. The difference was significant (P< 0.05).Conclusion: Grade 5, presence of ulcers and bacteria such as staphylococcus aureus and gram- negative organisms were major riskfactors for the surgical management of diabetic foot ulcer.